Expression Level of Keratin 7 in Epithelial Ovarian Cancer and Malignant Metastasis of Benign Epithelial Ovarian Tumors: Level of Keratin 7 in Epithelial Ovarian Cancer - Lin, Minghui; Wang, Jinhua; Wang, Shaoyu; Huang, Yuxiu (Cellular and Molecular Biology, 2022)
It was to investigate the diagnostic value of keratin 7 (KRT7) in malignant metastasis of epithelial ovarian cancer and benign epithelial ovarian tumors. From January 2018 to January 2019, 30 fresh tissues of benign epithelial ovarian tumors, 30 fresh tissues of borderline tumors, 30 fresh tissues of metastatic ovarian were collected in The First Affiliated Hospital of Fujian Medical University, and 30 fresh tissues of normal ovarian tissues were collected as the control group. Federation of gynecology and obstetrics (FIGO) staging criteria: 25 cases of stage I, 26 cases of stage II, 16 cases of stage III, and 23 cases of stage IV. The relative expression of KRT7 was detected by real-time fluorescence quantitative PCR, and the relationship between KRT7 expression and epithelial ovarian cancer grading was analyzed. The results showed that the positive expression rate of KRT7 was 12.1% in normal ovarian tissues, 28.4% in benign epithelial ovarian tumors, 53.5% in borderline tumors, and 24.2% in metastatic ovarian cancer. With the increase of tumor stage malignancy, the relative expression of KRT7 decreased significantly, but there was no significant difference between stage I and stage II, stage III and stage IV (P > 0.05). The difference between stage I and stage III, and stage IV was significant (P < 0.05). Patients with epithelial ovarian cancer had a significant difference compared with the control group (P < 0.05). In summary, compared with the control group, the expression of KRT7 in patients with benign epithelial ovarian tumors and borderline tumors was significantly decreased. The expression level of KRT7 in benign epithelial ovarian tumors was lower than that in borderline tumors. The expression of KRT7 was related to the occurrence, development, and deterioration of ovarian cancer, which provided a basis for targeted therapy of tumors.